Design and Development of a VHF Telemetry Two-way Radio Device Network Downtime/Uptime Alerting Prototype - Chisapi, Jonathan; Lubobya, Charles S (American Journal of Computing and Engineering, 2022)
This paper presents the design and development of a VHF telemetry Two-way radio device network downtime/uptime alerting prototype. Telemetry network monitoring using VHF 2-way radio Streaming is a paradigm in networking management that has not been deployed. The framework enables continuous monitoring of the mobile and fixed access points of the mining fleet management Wi-Fi system (in the case of the Barrick Lumwana mine, Zambia). Considering the significance of real-time alerts in a mining facility, critical systems such as slope monitoring radars, mobile emergency alerts, and timely copper production reports must be monitored in real-time. The results for the performance warnings of the telemetry access points collectively accounted for a response alert time of 1999ms from the samples collected which translated to 0.29% compared to the SNMP system that registered a total of 689500ms for the samples collected which translates to 99.71% of the total response time of 691499ms. The results derived from the VHF 2-way radio telemetry prototype show that this system performs better than the traditional SNMP network monitoring system. We recommend that this IP network prototype is used in open-pit mines alongside Motorola telemetry two-way radios.